Development and robust controller design for underactuated underwater glider platform for UMP lake monitoring - Mat-Noh, Maziyah; Zain, Zainah Md; Pebrianti, Dwi; Irawan, Addie; Daud, Mohd Razali (2016)
The autonomous underwater glider (AUG) demonstrates highly nonlinear and complexity in its dynamic model and also coupled with external underwater environment and disturbance. With limited actuators, the only option that AUG has in facing such environment and disturbances is by using strategies of control algorithm. For this reason, the main objective of this research is to formulate the control law that has the capability in facing the external disturbances and uncertainties due its hydrodynamics coefficients. As a result, a robust and reliable has been designed using quasi sliding mode control algorithm (QSMC) for the linearised model of longitudinal plane of an AUG. The performance of QSMC has been compared to linear quadratic regulator (LQR). The simulation results have shown that the proposed controller provides the smallest two times faster settling time than LQR. The prototype of the AUG has been successfully developed and test in water tank environment.